The Book of Tobit : texts from the principal ancient and medieval traditions : with synopsis, concordances, and annotated texts in Aramaic, Hebrew, Greek, Latin, and Syriac - Weeks, Stuart; Gathercole, Simon J.; Stuckenbruck, Loren T. (Berlin ; New York : Walter de Gruyter, 2004)
The relationships between the many different versions of Tobit present a famous and important problem for text-critics and historians of Judaism; however, study of the subject has been hindered by the lack of any single, reliable collection. This book brings together, for the first time, a wide range of texts (Greek, Latin, Hebrew, Aramaic, Syriac), some previously overlooked or virtually inaccessible, based in many cases on new readings. A single system of verse numeration is applied to all, and the key versions are presented synoptically, to facilitate comparison. Introductions and critical notes are provided for each text, along with succinct observations on the relationships between them in each passage, and concordances to assist stylistic and linguistic study.
Includes bibliographical references.
Text in Aramaic, Greek, Hebrew, Latin, and Syriac; introductions and critical notes in English.
Description based on print version record.
Keywords: Bible. -- Versions; Bible. -- Concordances; Tobit (bijbelboek); Bible. -- Versions; Bible. -- Concordances; Tobit (bijbelboek); Tobit <Buch>; Textkritik; RELIGION / Biblical Studies / Bible Study Guides; Konkordanz; Electronic books